102 Predictors of Spinal Cord Stimulation Success. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - De La Cruz, Priscilla; Roth, Steven G.; Campbell, Joannalee C.; Haller, Jessica; Wilock, Meghan; Lange, Steven; Pilitsis, Julie G.
Abstract: INTRODUCTION: As many as 30% of spinal cord stimulation (SCS) patients fail to obtain long-term pain coverage, even with the strictest parameters of a successful trial, unremarkable psychological assessment, and ideal placement of the permanent device. Why these patients either never receive adequate benefit or lose benefit remains elusive. METHODS: We performed a retrospective review of our prospective database of SCS patients undergoing surgery for routine indications. Six-month postoperative follow-up data were available for 45 patients. A score for global impression of outcome (1-10, with 10 being the best) was given by 2 reviewers who saw the patients preoperatively and throughout follow-up. Their scores were blinded from one another. A score of 5 was conservatively chosen as a success. The impact of Body Mass Index (BMI), random drug screen results, workers' compensation status, depression, and smoking were assessed. RESULTS: We report a phi correlation of 0.350 between smoking and failure ( P = .019). Further, there is a trend of correlation (phi = 0.286) between drug use and patients (n = 3) who underwent device removal ( P = .055). In this cohort, worker's compensation status, BMI, and depression did not impact outcome. CONCLUSION: Tobacco use correlates with less success with SCS at 6-month follow-up. Whether that is because of issues with healing and our transmission of signals to the periphery warrants further exploration. These data provide further evidence that tobacco cessation is important to surgical results.